Bias in the measure of the effectiveness of seasonal influenza vaccination among diabetics. Issue 6 (December 2016) - Casanova, Ludovic; Gobin, Nirvina; Villani, Patrick; Verger, Pierre
Highlights: Many outcomes based on morbimortality have measured the seasonal influenza vaccine's effectiveness on patients with diabetes aged 65 and higher. For working-age patients with diabetes, studies are rare and the effectiveness measured sometimes non significant for some outcomes. Several biases restricted the demonstration of the seasonal influenza vaccine's effectiveness for patients with diabetes. The residual confounding between vaccinated and non-vaccinated diabetics has been measured by analysing the persistence of a decrease of morbimortality other than during influenza season. It would be interesting in future works to use this approach in order to test the effect of adjustment of the healthy vaccine bias. Abstract: Background: The influenza virus is an important cause of morbidity and mortality for diabetics. The seasonal influenza vaccine's immunologic effectiveness is proven within the type 1 and type 2 diabetic populations, but the level of evidence is low. This article presents a systematic review for the bias in the measure of the effectiveness of seasonal influenza vaccination among diabetics. Methods: Using systematic review methods, we searched three electronic databases for published literature (MEDLINE, EMBASE and the Cochrane Library) and two grey literature (SIGLE and NHS EED) databases, to identify studies published between 1997 and 2013, examining the effect of seasonal influenza vaccination, among diabetics, on any measure for influenza morbidity or mortality. Results: 725 records were identified from the three databases and screening, short-listing was undertaken independently by two reviewers. After de-duplication, all records were screened by title and then abstract, and 34 short-listed records were reviewed in full, with 7 studies included: 4 cohort studies and 3 case–control studies, conducted in 7 countries. The most common outcome of interest in studies ( n = 4) was all-cause mortality among elderly diabetics (>65 years), with individual studies reporting reductions in risk of between 33% [95%CI: 4%–54%] and 68% [95%CI: 58%–75%]. We found only two studies for working-age adult diabetics: one reporting that vaccination prevented hospitalizations due to pneumonia or influenza (vaccine effectiveness [VE] 43%, [95%CI: 28%–54%]) and all-cause hospitalizations (VE: 28% [95%CI: 24%–32%]); and, another reporting no significant decrease in all-cause mortality for working-age adult diabetics. We have identified three major biases: the use of indirect health outcomes, a risk of selection bias (health-seeking bias), and no adjustment for participant pneumococcal vaccination status. The most recent included article finds that morbimortality is still lower during off-season influenza in both vaccinated and non-vaccinated diabetics, indicating important residual confounding. Conclusion: To date, the strength of evidence supporting the routine use of seasonal influenza vaccination is low for diabetics older than 65, and very low for working-age diabetics.